LEARNING ABOUT REFUGEE LIFE WITH EDUCATIONAL VIDEO GAMES - Elena Shliakhovchuk (Інформаційні технології і засоби навчання)
In recent years, scholarly investigations have yielded the consensus that video games possess multifaceted attributes that extend beyond their conventional perception as mere sources of leisure, diversion, and entertainment. The immersive nature of video games has led to increased interest in their use as platforms for engaging in discourses across a diverse array of subject matters with the potential to reach a wider audience and generate meaningful impact. Combined with the sense of presence and ownership that allows players to be placed in the shoes of characters grappling with social or political issues, video games are converting into an effective and accessible tool for learning and engagement with pressing cultural, social and political issues. Current research aims to understand better the potential of educational video games to address these pressing problems, in this case, the refugee crisis, to evoke empathy and raise awareness by looking at the problem 'behind the scenes' with an audience that initially was not interested in the topic. This qualitative study (N=78) employed the narrative research method to examine experiential participatory learning with participants playing the educational video game Against All Odds developed by UNHCR. By immersing players in this virtual experience, this game was created to educate and encourage a greater understanding of the realities faced by refugees, the complexity, and dangers of the refugee experience, as well as the reasons behind their displacement. The promising results of the research show that a video game can address serious social issues by creating a simplified but still dynamic scale model of refugee reality. Participants reported an enjoyable gaming experience, newfound interest in the issue at hand, increased empathy toward refugees, and motivation to help people in need. The study illustrates that by putting players in the shoes of struggling characters, video games could make learning about these topics more engaging and, as a result, more accessible and appealing to a wider audience, including non-gamers and people previously disinterested in the topic. These results invite educators, researchers, and scholars from the fields of education, game studies, social sciences, and cultural studies to explore the potential of video games as a possible tool for engaging students, addressing social issues, raising awareness, and fostering empathy. The article also identifies several prospective domains for future research.